INTEGRATION OF ISLAMIC VALUES IN SOCIAL STUDIES LEARNING IN ISLAMIC ELEMENTARY SCHOOL AL-ISLAMIYAH BANGKAR, MUARA UYA DISTRICT - Salabiyah, Salabiyah; Abdul Aziz, Abdul Rashid (SERUMPUN : Journal of Education, Politic, and Social Humaniora, 2023)
General learning that is integrated with Islamic Elementary School values hasmade learning more interesting, and more serious and active in following the learning.  Based on this statement, this research aims to find out how to integrate Islamic Elementary School values in social studies learning at Islamic Elementary School Al-Islamiyah Bangkar, Muara Uya District, and what IslaIslamic Elementary Schoolvalues are integrated in social studies learning at Islamic Elementary School Al-Islamiyah Bangkar, Muara Uya District. The subjects in this study were 1 social studies teacher at ISLAMIC ELEMENTARY SCHOOL Al-IslamiyahElementary Schoolyah Bangkar, Muara Uya District.  The techniques used in data collection are interviews, observations, and documentaries. Then it is processed through the process of data reduction, data display, and data verification. Meanwhile, to analyze the data, the author uses descriptive and qualitative analysis. After the data is analyzed, it can finally be concluded that the integration of IslaIslamic Elementary School values in social studies learning at Islamic Elementary School Al-Islamiyah Bangkar, Muara Uya District, can be concluded, that; 1) Social studies teachers have integrated Islamic Elementary School values in their learning.  Every material presented is integrated with Islamic Elementary School values, such as human material as social beings, universe material, historical material, and other materials. 2) Social studies teachers have integrated Islamic Elementary School values in their learning. The Islamic Elementary School values are integrated, such as establishing good relations with others in accordance with Islamic Elementary School teachings, maintaining mutual harmony in society, respecting each other, giving to each other, and also helping each other. Other Islamic Elementary School values are also such as behaving or having good rights among others, not offending anyone, thanking Allah SWT's favors, and believing in Him